Diagnosis and Management of Sphenoid and Ethmoid Fungal Sinusitis - Komang Tri Parama Arthika; I N Wartawan (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Rhinosinusitis is a common disorder affecting 20% of the population. Chronic sinus infections unresponsive to antibiotics should raise suspicion for fungal rhinosinusitis. Various types of fungi cause inflammation of the sinus mucosa. Sinusitis is an inflammation of the mucosa of the paranasal sinuses that can be caused by viruses, bacteria, parasites, or fungi. Fungal sinusitis is the rarest form of sinusitis. Fungal sinusitis can be classified based on the severity into invasive and non-invasive types. The severity of fungal sinusitis depends on the patient's immune status. Consequently, invasive fungal sinusitis often occurs in patients with chronic diseases that impair the immune system, such as diabetes mellitus (DM). This condition can lead to dangerous complications, including the rapid spread of the fungus to the eyes, brain, and surrounding tissues. Therefore, the diagnosis and management of invasive fungal sinusitis should be conducted promptly and accurately. The incidence of fungal sinusitis is rarely encountered; however, in recent decades, the incidence has been reported to be increasing. In Asia, the incidence of fungal sinusitis accounts for 42% of all rhinosinusitis cases. Symptoms vary depending on the patient's immune status. CT scan is one of the imaging methods that can be used to assist in the diagnosis of invasive fungal sinusitis and provide important information for appropriate management, leading to more accurate and rapid treatment. Fungal sinusitis occurs when airborne fungi adhere to the mucous membrane of the nasal cavity and sinuses through respiratory inhalation. Fungal sinusitis manifests in various forms, ranging from simple irritation of the sinus mucosa to life-threatening disease. Fungal sinusitis may be asymptomatic, but common symptoms include purulent rhinorrhea, facial pain, and postnasal drip. Diagnosing fungal sinusitis through nasal endoscopy is challenging. In computed tomography (CT), fungal sinusitis is characterized by observations such as calcifications, heterogeneous soft tissue density lesions, and periosteal thickening. The treatment involves endoscopic removal of fungal masses, which fully widen the sinus ostium8.